Determinants of Capital Structure on Trading and Manufacturing Enterprises: A Case of Nepal - Dhodary, Shanker (NCC Journal, 2019)
This study mainly aimed at examining the determinants of capital structure in Nepalese trading and manufacturing firms. The study has covered eleven major on-financial enterprises of trading and manufacturing firm’s specific variables. Firm’s size, growth opportunity, asset tangibility, profitability, firm’s age, liquidity and interest coverage ratio have selected as variables to examine their effect on corporate capital structure. The study used both descriptive and causal comparative research design to examine the determinants of capital structure. Data required for undertaking the study were collected from secondary sources. For each enterprise, financial data for 10 fiscal years covering the period of F/Y 2005/2006 to F/Y 2015/2016.The study concluded that asset tangibility, profitability, liquidity and interest coverage ratio are the major determinants of corporate capital structure in Nepalese trading and manufacturing firms.